Dose-intensive melphalan with stem cell support (CM regimen) is effective and well tolerated in elderly myeloma patients - A Palumbo; S Triolo; L Baldini; V Callea; A Capaldi; V De Stefano; M Grasso; M Liberati; C Lotesoriere; R Marceno; F Marmont; P Musto; et al. (Haematologica, 2000)
BACKGROUND AND OBJECTIVE: Multiple myeloma (MM) typically afflicts elderly patients. High-dose therapy has recently been shown to lead to a better outcome than standard treatment, mainly in younger patients. The extent to which older subjects can benefit from intensified approaches without excessive toxicity is examined in this study. DESIGN AND METHODS: Between December 1994 and May 1997, 12 Italian Multiple Myeloma Study Group institutions entered 68 patients at diagnosis (median age 65) into an intensified chemotherapy regimen: cyclophosphamide (CY) 3 g/m(2) plus melphalan 60 mg/m(2) followed by peripheral blood progenitor cells (PBPC) and G-CSF (CM regimen). CY (day 0) and G-CSF were used to mobilize PBPC harvested by a single leukapheresis on day 10. Melphalan was infused on day 11. PBPC were kept unprocessed at 4 degrees C for 48 hours and reinfused on day 12. Three CM regimens were delivered at 6-month intervals. RESULTS: Sufficient PBPC to support the first CM cycle were available (median CD34(+) harvest: 4.9x10(6)/kg), but dropped significantly after the second (median CD34(+) harvest: 2x10(6)/kg) and the third (median CD34(+) harvest: 0.9x10(6)/kg). The median durations of severe neutropenia (absolute neutrophil count < 500 microL) were 3, 4, and 3 days, and those of severe thrombocytopenia (platelets < 25,000/microL) were 2.5, 2, and 1 days, after the first, second and third courses, respectively. The frequency of extramedullary toxicities was low. Treatment-related mortality (TRM) was 3% after the first CM, only. Complete remission (CR) was 14% after the first, 16% after the second and 27% after the third CM. After a median follow-up of 34 months (range 19-49 months), median event-free survival was 35.6 months. INTERPRETATION AND CONCLUSIONS: These results indicate that dose-intensity of melphalan can be increased by reinfusing PBPC with acceptable low toxicity. The combination of CY and melphalan followed by PBPC is an effective chemotherapy for elderly myeloma patients. Repeated melphalan infusion hampered subsequent CD34(+) harvests.